Sustainability in air transportation from Islamic perspective - Sahrir, Syazwani; Ibrahim, Mansor; Bachok, Syahriah; Mohamed Osman, Mariana; Abdullah, Alias (2012)
Air travel is the fastest growing mode of transportation, becoming ever more popular and frequent. The growing pervasiveness of air travel can be seen by airport infrastructure upgrading and the increasing numbers of airports today. The majority of aircraft need an airport with the infrastructure to receive maintenance, restocking, refueling and for the loading and unloading of crew, cargo and passengers. Recent social movements have alerted public opinion and political administrations to the safety of the areas surrounding airports and the negative externalities produced by airport developments. Due to the increasing importance of enlargements in airport capacity this has become a hot topic for policy makers and academics. At the same time, growing concerns and interests in Islamic perspectives on matters such as transportation has been witnessed in the current trend. The applications of Islamic principles are the conventional approaches towards sustainability. Transportation is to serve people purposes to undertake the worldly activities in search for a better, longer and prominent lifetime in the Hereafter. As such, the use of transportation modes such as air transportation should take the cognizance of the Islamic perspectives on nature of humanity, people needs, habits, behavior and the synergistic effects of the movement on the environment.